Night-Market Traders Are They Entrepreneurial or Just Making Ends Meet? - Isa, Azwardi Md; Azman, Noor Azura; Sukri, Nur Syazwani Aisyah Ahmad (UI Scholars Hub, 2020)
Research Aims - Night-market is a popular type of micro-business in Southeast Asia. The purpose of this research is to examine night markets from the perspective of business development, a perspective that has received limited attention from the literature. Design/methodology/approach - A total of 300 questionnaires were distributed amongst nightmarket business owners in a selected venue around Penang. Data were analyzed using SEM-PLS to measure the variables proposed in the study. Research Findings - The results of this study showed that commitment and business experience is significantly related to business development while government assistance yields no relationship. The age of the business owner has a significant moderating impact on the effect of commitment and business experience on business development and, again, no impact on the effect of government assistance. Theoretical Contribution/Originality - This study argues that the presumption that all microbusinesses have an entrepreneurial character should be treated with skepticism. It is important to differentiate between being entrepreneurship and making end meets. Managerial Implication in the South East Asian context - Managerial Implication in the Southeast Asian Context: The present study suggests that operating a night-market business and passing it down from generation to generation while at the same time aiming for it to grow bigger is unrealistic. Research limitation & implications - This study has several limitations. First, due to time and geographical constraints, the sample size was limited to 300, and the data were collected only in Penang. Secondly, the study did not consider whether the business owners (night-market traders) were first generation owners, second generation, or beyond.